EPIDEMIOLOGICAL PROFILE OF BREAST CANCER IN A REFERENCE HOSPITAL IN THE NORTH REGION - Rocha, Francianne Silva; Silva, Wellington dos Santos; Nascimento, Eliude Rodrigues do; Bacciotti, Alessandra Marques (Mastology, 2018)
Introduction: Breast cancer is a public health issue, not only in underdeveloped countries, as is the case of Brazil, but also in developed ones, such as the United States and some Western European countries. The frequency of distribution of different types of cancer varies according to the characteristics of each region, which emphasizes the need to study geographical variations, risk factors, and disease patterns that pervade regional particularities. Objective: The present study describes the epidemiological profile of patients treated at a reference cancer hospital in the North Region of the country and determines the variables of clinical and epidemiological interest related to risk factors for breast cancer. Methods: This is a cross-sectional descriptive study conducted through interviews and analysis of medical records of 114 patients treated at Hospital Ophir Loyola between 2016 and 2017 in the city of Belém, Pará. Data were presented as absolute and relative frequencies. Results: Most women who participated in the study were multiracial, overweight, with a mean age of 51 years, and had low schooling. A little over half of them were born in the inland of the state; the majority lived in the metropolitan area of Belém, 42% in the inland, and only 11% in the countryside. The mean interval between clinical suspicion and diagnostic confirmation was almost 13 months. The most frequent histopathological classification was invasive ductal carcinoma, and the immunohistochemical profile with the higher incidence was luminal B, followed by luminal A. Conclusions: Overweight, considered a risk factor for breast cancer, is modifiable, which underlines the importance of awareness actions for early diagnosis, knowledge of the disease, and encouragement to physical activity and healthy eating habits, in order to reduce morbidity and mortality, and improve the prognosis of women affected by this pathology.